iPhone Design Award-Winning Projects - Danneni, Chris (Apress, 2012)
This is a book about building apps with good design, parsimonious code and aesthetic appeal on the Apple iPhone and iPod Touch. At times, this book references code and give sample projects; other times, it delves into interaction and visual design. It doesn’t take a CS doctorate to appreciate or even understand, but some familiarity with programming is assumed.$